LIFE-HISTORY AND FEEDING HABITS OF THE SPOTTED SEER SCOMBEROMORUS GUTTATUS (BLOCK & SCHNEIDER) - Vijayaraghavan, P (Indian Journal of Fisheries, 2016)
THE available information relating to marine fish eggs and larvae of Madras is covered by the accounts given by John (1951) and Nair (1952 a â€¢+ b). In the present paper, which deals with part of the results of the investigation undertaken by the author at the Zoological Research Laboratory, University of Madras, for three years (1950-53), on fish eggs and larvae occurring in Madras plankton, the methods of collection, of hatching of the eggs and of rearing the larvae in general are given, together with observations on the life-history of Scomberomorus guttdtus vidth its food and feeding habits. Our knowledge of the life history of this fish is confined to Delsman’s (1931) description of its eggs and larvae reared up to the third day